2021
DOI: 10.19182/bft2021.348.a36399
|View full text |Cite
|
Sign up to set email alerts
|

Vingt-deux espèces d’arbres autochtones plantées en arboretum à Korhogo au nord de la Côte d’Ivoire : trois décennies de suivi

Abstract: En Afrique tropicale, dans les plantations forestières, la majorité des espèces autochtones ont été délaissées au profit d’espèces exotiques à croissance initiale rapide. Cette tendance est encore plus marquée dans les zones soudanienne et soudano-guinéenne à longue saison sèche. Ainsi s’explique le manque de connaissances sur les potentialités et la sylviculture des espèces d’arbres autochtones ou « locales ». Pour contribuer à l’acquisition de ces connaissances indispensables, un arboretum de 2,56 ha a été i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…They play an important role in forest ecosystem functions and carbon dynamics (Kull & Laris, 2009;Lehmann et al, 2014;Shlisky et al, 2009). Their dynamics in the landscape is one of the most addressed topics by the scientific community regarding phenomenon effects on all the components of the environment, in particular vegetation, fauna, soil, water and air (Aubréville, 1953(Aubréville, , 2013Louppe & Oliver, 2004;Louppe et al, 1995;N'Dri et al, 2012N'Dri et al, , 2014. Several authors reported wildfires as a climate-induced disturbance (Jolly et al, 2015;Kouassi et al, 2018;Laris, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…They play an important role in forest ecosystem functions and carbon dynamics (Kull & Laris, 2009;Lehmann et al, 2014;Shlisky et al, 2009). Their dynamics in the landscape is one of the most addressed topics by the scientific community regarding phenomenon effects on all the components of the environment, in particular vegetation, fauna, soil, water and air (Aubréville, 1953(Aubréville, , 2013Louppe & Oliver, 2004;Louppe et al, 1995;N'Dri et al, 2012N'Dri et al, , 2014. Several authors reported wildfires as a climate-induced disturbance (Jolly et al, 2015;Kouassi et al, 2018;Laris, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…After a period of root inactivity due to the displacement from their initial growth environment to another, they resume growth but develop a shallower root system, which hampers them during periods of high temperatures and/or pronounced water deficit (Zhang et al 2021). This results in an increased risk of mortality (Hérault et al 2020, Louppe et al 2021. Another factor that leading to a low level of diversity of planted trees in cocoa farms is the farmer's level of education (schooling).…”
Section: Planted Trees Exhibit High Complementarity With Other Treesmentioning
confidence: 99%